Phenotypic plasticity: a useful framework for understanding adaptation in forest species - Chambel, M.R..=700 1 Climent, J.; Alia, R.; Valladares, F.
(Es, En)
ilus., 78 ref.
Keywords: GENOTIPOS; FENOTIPOS; GENES; DESARROLLO BIOLOGICO; MODELOS; GESTION; ARBOLES FORESTALES; MEDIO AMBIENTE; ESPAÑA; FLEXIBILIDAD FENOTIPICA; PLASTICIDAD EN EL DESARROLLO; PLASTICIDAD TRANSGENERACIONAL